Sharia-Compliant And Islamic Governance On Financial Performance In Indonesian Islamic Bank - Andy Putra Wijaya; Rusdianto Rusdianto; Nur Faphuss Ikrimah; Ngazzah Hanun Nabilah; Nikita Khairunissa; Nur Alfiah Madaniah (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
This research aims to analyze the relationship between Sharia Compliance and Islamic Governance on the financial performance of Islamic banking in Indonesia. Islamic banking has experienced significant growth in recent years, but there are still differences in performance between Islamic and conventional banks. Therefore, this research aims to examine the relationship between compliance with Sharia principles and the implementation of Islamic governance, which affects the financial performance of Sharia banks. This study uses a descriptive-analytic approach by collecting secondary data from Islamic bank financial reports and the Islamic Governance Index. The data was analyzed using the regression method to identify the relationship between Sharia Compliance, Islamic Governance, and the financial performance of Islamic banks. This research shows that Sharia Compliance has a significantly favorable influence on the financial performance of Islamic Banking. Islamic banks that comply more with Sharia principles tend to perform better. Apart from that, Islamic governance also has a significantly favorable influence on the financial performance of Islamic banks. Sharia banks that implement good Islamic banking governance have more robust financial performance. Limitations of this research include the limited secondary data available and the focus on the Islamic banking industry in Indonesia. Future research could involve field research, primary data, and expanded geographic coverage to understand better the relationship between Sharia Compliance, Islamic Governance, and Islamic Banking financial performance.